2015
DOI: 10.1155/2015/284071
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic, Flavonoid, Tomatine, and Tomatidine Contents and Antioxidant and Antimicrobial Activities of Extracts of Tomato Plant

Abstract: The purpose of this study was to evaluate the antioxidant and antimicrobial properties of extracts of different fractions of two tomato plant cultivars. The stems, roots, leaves, and whole-plant fractions were evaluated. Tomatine and tomatidine were identified by HPLC-DAD. The leaf extracts from the two varieties showed the highest flavonoids, chlorophyll, carotenoids, and total phenolics contents and the highest antioxidant activity determined by DPPH, ABTS, and ORAC. A positive correlation was observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
4
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 45 publications
(60 reference statements)
8
71
4
3
Order By: Relevance
“…(a), using the TEAC assay. Previous studies reported that rutin and phenolic acids can contribute to the overall antioxidant capacity of tomato, neutralizing free radicals by acting as electron donors or inhibiting the activity of enzymes involved in the production of free radicals . Our results indicated a slight, not significant, higher antioxidant activity in E32, followed by E17 and E30.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…(a), using the TEAC assay. Previous studies reported that rutin and phenolic acids can contribute to the overall antioxidant capacity of tomato, neutralizing free radicals by acting as electron donors or inhibiting the activity of enzymes involved in the production of free radicals . Our results indicated a slight, not significant, higher antioxidant activity in E32, followed by E17 and E30.…”
Section: Resultssupporting
confidence: 50%
“…In fact, genes implicated in polyphenol biosynthesis are activated by light exposure, and a ‘sunscreen’ function has been proposed for these phytochemicals to protect the tissues from possible damage generated by UV radiation . Some authors reported that high temperatures and light exposure stimulate the production of phenolic acids and other flavonoids . Indeed, heat stress positively modulates the activity of the enzyme phenylalanine ammonia‐lyase and affects the total phenols content by activating their biosynthesis and inhibiting their oxidation in tomato plants …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that majority of the polyphenols and flavonoids present in T. daniellii leaves may be structurally polar in nature. Previous study had shown that some polyphenols and flavonoids are structurally polar with antioxidant activity [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have also been reported by Titley and others in 2004. [17][18][19][20] On evaluating the groups that were surface treated before bonding (Groups III, IV, V ) , it is evident that all the experimental groups have performed significantly better than the control groups(Group I, II). This clearly indicates that surface treatment with these agents have resulted in improved shear bond strength of composite to bleached enamel surface.…”
Section: Discussion:-mentioning
confidence: 99%